A new species of Cnemaspis (Sauria: Gekkonidae) from Northern Karnataka, India - Srinivasulu, Chelmala; Kumar, Gandla Chethan; Srinivasulu, Bhargavi (Zootaxa, 2015)
A new species of rupicolous gecko of the genus Cnemaspis is described from Hampi, Karnataka, southern India. Cnemaspis adii sp. nov. is diagnosable from all the Indian congeners in possessing the following suite of characters: medium-sized Cnemaspis, SVL less than 35 mm (31.7–34.9). Dorsal scales on the trunk homogeneous, small, granular and feebly keeled. Spine-like tubercles absent on the flanks. Mental subtraingular, two pairs of postmentals, primary pair separated by a single chin shield. Ventral scales on the trunk smooth, imbricate; 22–26 scales across the belly. Supralabial I narrowly in contact with nasal. Dorsal aspect of forelimbs and hindlimbs are weakly unicarinate. Lamellae under the digit IV of pes 20–22. Males with two precloacal pores, two femoral pores on each side of the thigh. The existence of the species in a World Heritage Site with continuous anthropogenic interference ascertains the robustness of the species and need for additional herpetofaunal explorations to reveal the total diversity of species of the genus Cnemaspis in peninsular India.